Bond repurchase objectives and the repurchase method choice - Levy, Hagit; Shalev, Ron (Journal of Accounting and Economics, 2017)
This study investigates how firm׳s bond repurchase objective affects its choice of repurchase method. Unlike tender offers, open-market repurchases are not pre-announced and buyer׳s identity is unknown to the seller. We provide evidence that firms are likely to repurchase on the open-market when bonds are mispriced and when firms seek to manage their financial reports, either to meet earnings targets or avert debt covenant violations. When firms seek to amend indenture terms, they prefer tender offers. We also find that firm׳s information quality affects the likelihood of mispricing exploitation behavior and that insiders buy firm׳s stocks around open-market repurchases.